Duodenal Atresia in Finland from 2004 to 2017: Prevalence, Mortality, and Associated Anomalies—A Population-Based Study - Alikärri, Suvi; Helenius, Ilkka; Heiskanen, Susanna; Syvänen, Johanna; Kemppainen, Teemu; Löyttyniemi, Eliisa; Gissler, Mika; Raitio, Arimatias (European Journal of Pediatric Surgery, 2024)
Introduction Duodenal atresia (DA) is the most common atresia of the small bowel. This study aims to assess the prevalence, mortality, and associated anomalies related to DA in Finland from 2004 to 2017.Material and Methods A nationwide study based on registers maintained by the Finnish Institute for Health and Welfare and Statistics Finland containing data on all live births and stillbirths and terminations of pregnancy. The cases were identified based on the ICD-9 and 10 (International Classification of Diseases revisions 9 and 10) codes. Associated anomalies were classified based on the EUROCAT criteria; minor anomalies were excluded.Results There were 249 DA cases including 222 (89.2%) live births, 16 (6.4%) stillbirths, and 11 (4.4%) terminations. There was no significant change in the prevalence rates between 2004 and 2017. Live birth prevalence was 2.75/10,000 and total prevalence was 3.08/10,000 births. A total of 100 (40.2%) cases were isolated, 67 (26.9%) had other multiple congenital anomalies, and 83 (33.3%) were syndromic. There were no terminations in isolated DA. Most associated anomalies were cardiac (36.1%), followed by other gastrointestinal tract anomalies (23.7%) and limb deformities/defects (7.2%). Trisomy 21 was observed in 63 cases (25.3%). Neonatal mortality was 3.6% (n = 8) and at 1 year 95.0% were alive. Both neonatal and infant mortalities were associated with cardiac anomalies (p < 0.001 and p = 0.001, respectively). All neonatal deaths had associated cardiac defect(s).Conclusions The prevalence of DA in Finland remains stable and among the highest reported. DA is often associated with cardiac anomalies, which portend a high risk for mortality. Despite the burden of associated anomalies, overall survival is high.
Keywords: duodenal atresia; mortality; prevalence; associated anomalies